Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3892/mmr.2022.12812
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CXCL8 and its receptors CXCR1/CXCR2 at the mRNA level in neoplastic tissue, as well as in serum and peritoneal fluid in patients with ovarian cance

Abstract: Understanding the relationship between the coexistence of inflammatory and neoplastic processes in ovarian cancer, particularly those involving chemokines and their receptors, may help to elucidate the involvement of the studied parameters in tumor pathogenesis and could lead to improved clinical applications. Therefore, the present study aimed to analyze the levels of C-X-C motif chemokine ligand 8 (CXCL8), and its receptors C-X-C chemokine receptor (CXCR)1 and CXCR2, in the serum and peritoneal fluid of wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(61 reference statements)
0
0
0
Order By: Relevance
“…Malignant ovarian neoplasms have complex TME, which causes changes in cytokine production as exhibited in peritoneal fluid [14][15][16][17][18], and tumor tissue [18]. Furthermore, studies have revealed systemic changes in cytokine production in ovarian cancer women [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant ovarian neoplasms have complex TME, which causes changes in cytokine production as exhibited in peritoneal fluid [14][15][16][17][18], and tumor tissue [18]. Furthermore, studies have revealed systemic changes in cytokine production in ovarian cancer women [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Malignant ovarian neoplasms have complex TME, which causes changes in cytokine production as exhibited in peritoneal fluid [14][15][16][17][18], and tumor tissue [18]. Furthermore, studies have revealed systemic changes in cytokine production in ovarian cancer women [17][18][19][20]. The immune response study in these compartments can assist in better understanding of immune response against ovarian cancerous tumor and tumor escape mechanisms.…”
Section: Introductionmentioning
confidence: 99%